Obesity leads to impairments in the morphology and organization of human skeletal muscle lipid droplets and mitochondrial networks, which are resolved with gastric bypass surgery‐induced improvements in insulin sensitivity. (10th June 2018) - Kristensen, M. D.; Petersen, S. M.; Møller, K. E.; Lund, M. T.; Hansen, M.; Hansen, C. N; Courraud, J.; Helge, J. W.; Dela, F.; Prats, C.
Abstract: Aims: Skeletal muscle lipid stores and mitochondrial function have been appointed as key players in obesity‐induced insulin resistance. However, there are conflicting reports in the literature based on in vitro quantitative measurements. Here, we test the hypothesis that it is not the quantity but the quality that matters. Methods: This study combines quantitative and qualitative structural measurements of lipid stores and mitochondrial dynamics in skeletal muscle from lean subjects, and subjects with morbid obesity, with and without type 2 diabetes, before and after gastric bypass surgery. Results: The structural organization of muscle mitochondrial networks in type II muscle fibres from subjects with morbid obesity is impaired. In addition, the amount of skeletal muscle perilipin 2 protein per intramyocellular lipid is reduced in subjects with morbid obesity, resulting in qualitative alterations in perilipin 2 coat around some lipid droplets. Gastric bypass surgery‐induced weight loss and insulin resistance remission were associated with decreases in intramyocellular lipid stores and, qualitative improvements in lipid droplets' morphology, perilipin 2 coat and mitochondrial dynamics. Conclusion: Morbid obesity leads to severe qualitative alterations of both skeletal muscle lipid stores and mitochondrial networks. The degree of structural improvements after gastric bypass surgery was proportional to the improvements in whole body insulin sensitivity, suggesting an association between these events.